Active disturbance rejection control for uncertain time-delay nonlinear systems - Ran, Maopeng (2021)
This paper addresses the problems of design and analysis of active disturbance rejection control (ADRC) for uncertain nonlinear systems subject to input time-delay. A novel extended state observer (ESO) is first designed as a predictor to realize the predictive state, and the total uncertainty which represents the effects of the unknown nonlinear dynamics and external disturbance. Based on the output of the ESO, a predictive ADRC law is presented. Conditions for the resulting closed-loop system to achieve convergence are obtained. It is shown that the upper bounds of the ESO gains are limited by the time-delay. Numerical simulations are given to illustrate the theoretical results.